2021
DOI: 10.1101/2021.11.02.466954
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The effect of acute oral galactose administration on the redox system of the rat small intestine

Abstract: Galactose is a ubiquitous monosaccharide with important yet incompletely understood nutritive and physiological roles. Chronic parenteral D-galactose administration is used for modeling aging-related pathophysiological processes in rodents due to its ability to induce oxidative stress (OS). Conversely, chronic oral D-galactose administration prevents and alleviates cognitive decline in a rat model of sporadic Alzheimer’s disease indicating galactose may exert beneficial health effects by acting in the gut. The… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 77 publications
0
5
0
Order By: Relevance
“…The latter is further supported by the fact that the same biomarkers have been shown to be sufficiently sensitive to detect redox-related alterations induced by relatively mild stimuli (e.g. single orogastric administration of the 200 mg/kg D-galactose solution)[37] and in other neurotoxin-based models of brain-first-induced neurodegeneration [31, 32].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The latter is further supported by the fact that the same biomarkers have been shown to be sufficiently sensitive to detect redox-related alterations induced by relatively mild stimuli (e.g. single orogastric administration of the 200 mg/kg D-galactose solution)[37] and in other neurotoxin-based models of brain-first-induced neurodegeneration [31, 32].…”
Section: Discussionmentioning
confidence: 99%
“…Low molecular weight thiols (with glutathione (GSH) being the most abundant) and free protein sulfhydryls (SH) were quantified by measuring 5-thio-2-nitrobenzoic acid (TNB) following the reaction of 5,5⍰-dithio-bis(2-nitrobenzoic acid) (DTNB) with the supernatant and the pellet after precipitation of proteins with sulfosalicylic acid [31, 36, 37]. Briefly, 25 μL of each homogenate was incubated with 4% w/v sulfosalicylic acid in ddH 2 O for 1 h on ice in a 1:1 volumetric ratio.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A subtle point that should be considered in this study is switching the D‐galactose intake way from the mother's bloodstream during fetal life to the gastrointestinal tract during the infancy period by lactation. Recently, Homolka et al (2022) have shown that the small intestinal redox system is activated under high amounts of oral D‐galactose, creating a protective barrier against oxidative stress and protecting cells from oxidative damage. Oxygen metabolism produces superoxide (SO), which causes many types of cell damage.…”
Section: Discussionmentioning
confidence: 99%
“…Catalase-like activity CAT solution was prepared by dissolving 1 mg of lyophilized bovine liver CAT powder (Sigma Aldrich, USA) in 10 ml of phosphate-buffered saline (PBS) (pH 7.4). CAT activity was measured using the method first described by Hadwan [18] and adapted in [19]. Briefly, the samples were incubated with 50 μl of the substrate solution (2-10 mM H2O2 in PBS) and the reaction was stopped by adding 150 μl of the Co(NO3)2 stop solution (5 mL Co(NO3)2 x 6 H2O (0.2 g in 10 mL ddH2O) + 5 mL (NaPO3)6 (0.1 g in 10 mL ddH2O) added to 90 mL of NaHCO3 (9 g in 100 mL ddH2O)).…”
Section: Introductionmentioning
confidence: 99%